Elid superfinishing of spherical bearings - Raffles, Mark H. (Cranfield University, 2007)
Driven by a requirement to extend the lifespan of self-aligning lined spherical bearings, this research investigates the use of Elid (electrolytic in-process dressing) as a method of improving ball surface finish. Elid is a continuous and self-regulating electrochemical dressing process that modifies the surface of a grinding, lapping, or superfinishing wheel. It provides improved grit protrusion, impedes wheel loading / glazing and promotes effective cutting. The characteristics of the newly-developed Elid superfinishing process are in many ways fundamentally different to conventional superfinishing. The main difference is that the use of super-abrasives prevents the wheel from self-sharpening; the normal mechanism by which dulled conventional abrasives are removed and a wheel’s surface refreshed. Because the wheel’s performance and condition is continually maintained inprocess by the Elid system, metal resin bonded (MRB) wheels containing very small super-abrasives can be used. It is the utilization of these fine abrasives (30 to 0.12 μm) that enables surface roughness values below 5 nm Ra to be consistently produced on the spherical surface of corrosion-resistant steel balls. This research provides an in-depth understanding of the Elid spherical superfinishing process; investigating the most effective use of the Elid system, wheel dressing requirements and process performance. Optimisation is provided in terms of evaluating the critical operating parameters, the most effective superfinishing cycle and the implications to the complete ball production chain. A range of techniques are used to evaluate processing performance and ball output quality. These include in-process monitoring of Elid and wheel spindle power levels, analysis of wheel condition, rates of ball surface generation and material removal, ball finish and form. Although predominantly concentrated on corrosion-resistant steel, testing is also conducted on titanium and various ball coatings. In investigating various ways of using the Elid system, this work considers electrodischarge truing, pre-process dressing, Elid 1, Elid 2, Elid 3, and Elid combined with electrolytically assisted superfinishing. The initial process solution of Elid 3 (electrodeless) superfinishing provides the capability of working on all standard size balls, however the dressing system lacks stability. The development of a fixturing system that has a small separate electrode enables Elid 1 (conventional) to be used on the majority of ball sizes. Elid 1 allows more aggressive and consistent dressing, a faster rate of ball material removal and thus a substantially reduced processing time. Results with a #12,000 wheel show that surface quality is vastly improved through the use of Elid whilst maintaining current production standards of form accuracy. Surface finishes of 2nm Ra are achieved, which is an order of magnitude better than balls currently produced using barrelling / polishing. Processing times are equivalent or faster when using Elid 1. Alternatively, consistently sub 10 nm Ra finishes can be reached with a #2,000 wheel using Elid 2 (interval dressing). Generally MRB-CBN wheels provide a more effective carbide cutting action than conventional superfinishing wheels. Controlling wheel condition and achieving full and even ball to wheel conformity are the two most significant contributory factors to the success of Elid spherical superfinishing. Insufficient control of these factors results in poor output quality. Monitoring of wheel spindle and Elid power usage provides useful information in assessing the condition of the wheel and identifying potential problems. High spindle power correlates with fast material removal and is a result of high loads and a free cutting action. Elid processing can be employed for improving surface finish after the conventional honing stage, or after cylindrical grinding for improving both ball form and finish.